2017
DOI: 10.1111/all.13238
|View full text |Cite
|
Sign up to set email alerts
|

Meat allergy associated with galactosyl‐α‐(1,3)‐galactose (α‐Gal)—Closing diagnostic gaps by anti‐α‐Gal IgE immune profiling

Abstract: Detection of individual sensitization patterns with different α-Gal-containing analytes provides the basis for an individual allergy diagnosis for α-Gal-sensitized patients. Higher amounts of α-Gal in pork and beef innards compared to muscle meat as indicated by a higher staining intensity are a plausible explanation for the difference in allergic symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
3
29
0
3
Order By: Relevance
“…2 ). The typical pattern for IgE against α-Gal (associated with meat allergy) could be identified for serum ADL86 as IgE binding to CTX, HSA-α-Gal and bovine TG 27 . No binding to glycan-processed CTX, to unconjugated HSA or human TG was detected, indicating the glycan-dependency.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The typical pattern for IgE against α-Gal (associated with meat allergy) could be identified for serum ADL86 as IgE binding to CTX, HSA-α-Gal and bovine TG 27 . No binding to glycan-processed CTX, to unconjugated HSA or human TG was detected, indicating the glycan-dependency.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy raises the question whether aGal in the salivary N-glycome of the tick alone is the RMA sensitization factor. In addition, as mentioned above, the sIgE-based diagnostic assay found that the assay results included a substantial portion of false-positive results and difficulties in prediction of the allergic clinical symptoms [51,56,57].…”
Section: Agal In the Tick Sg As The Sensitizer Of Red Meat Allergymentioning
confidence: 91%
“…Red meat allergy (RMA) is an allergic reaction to aGal caused by a hypersensitive IgE response upon recognition of the glycan epitope. Although aGal has been well documented as an elicitor of RMA, the diagnostic test also suffers from sIgE-based assays for false-positive results [50][51][52][53][54][55][56][57]. The aGal allergy is also highly relevant to hyperreactions to xenoplantation [58] and to anti-cancer therapy using the monoclonal antibody cetuximab [59].…”
Section: Agal In the Tick Sg As The Sensitizer Of Red Meat Allergymentioning
confidence: 99%
“…62 Cross-reactivity from the in vitro alpha-gal assay can occur with Bos d (beef) as a result of bovine thyroglobulin. 63 Although evidence exists for cross-reactivity with milk proteins, patients can generally tolerate low-fat milk and milkbased products.…”
Section: Ige To A-galmentioning
confidence: 99%